RAGAM BAHASA GAUL DI PASAR DAN TERMINAL BOJONEGORO - Abdul Syukur (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
This study aimed to describe the vocabulary based on change in the structure of the phonology, morphology, syntax and slang used bojonegoro society in the terminals and markets. Data collected by observation shaped tapping techniques, see, fishing rods and record. Method and data analysis is qualitative descriptive method and technique of distributional. The results of this study as follows. The first, phonological structure change slang. The second, the process of formation of morphologically vocabulary of slang include a) acronyms formed of two syllables beginning of the from the two words, two syllable the beginning of the two words, four syllables beginning of four words, b) affixation, c) reduplication d) inset –ok- e) suffix -ong and –ing vowel and consonant.